RE-REDUCTION OF THE OLD PHOTOGRAPHIC OBSERVATIONS OF INTERAMNIA (704) BASED ON GAIA DR2 REFERENCE CATALOGUE - Protsyuk, Yu. I.; Maigurova, N. V. (Одеські астрономічні публікації, 2020)
A new astrometric reduction of old photographic astroplates benefiting from integration of modern technologies such as the high precision digitizing machines and the high precision Gaia DR2 catalogue could be useful to study the orbital motion of Solar system minor bodies. Based on the newly released Gaia DR2 star catalogue, the scans of the photographic plates containing images of Interamnia (704) taken by the Zonal Astrograph of Mykolaiv Astronomical Observatory (MAO) in 1974- 1985 were re-reduced. For our investigation we used 29 plates from the UkrVO archive digitized by commercial EPSON scanner with 1600 dpi resolutions. Besides for 2 of them were digitized by the high precision digitizing machine of Shanghai Astronomical Observatory of the Chinese Academy of Sciences (ShAO) with 2540 dpi resolution. Almost all the plates have 3 exposures with a small shift. Each of 29 plates was scanned 6 times by EPSON scanner in 0° direction. The ShAO digitizing machine scanned 2 plates also 6 times but 3 times in 0° direction and 3 times in 90° direction. Totally, 85 asteroid positions taken from 29 plates were derived. Only 5 asteroid positions were calculated from ShAO scans. The full identification was conducted and coordinates of all objects were obtained with usage of different options of astrometric reductions. The mean inner accuracy of obtained asteroid positions is 0.03″ in RA and 0.14″ in DEC for EPSON scanner and 0.014″ in RA and 0.013″ in DEC for the ShAO digitizing machine in 0° direction and 0.010″ in RA and 0.011″ in DEC in 90° direction. The comparison of the new topocentric asteroid positions with Horizons ephemeris was made for calculation (O-C) residuals and their RMS. The mean residual differences between the scan obtained positions and JPL calculated positions were (0.09 ± 0.16)″ in RA and (-0.09 ± 0.25)″ in DEC for the MAO digitized plates; the calculated differences for the ShAO scans are close to zero. Comparison of the results obtained with previous reductions of these observations with Tycho2 and UCAC4 reference catalogues showed that the use of the Gaia DR2 reference catalogue does not lead to a significant improvement in the random and systematic component of the residual differences (O-C) for scans with EPSON scanner from the UkrVO archive. The results obtained by processing images with the ShAO digitizing machine suggest that in this case, the re-reduction of all photographic observations based on the Gaia DR2 could improve the accuracy of old photographic observations to the level of modern ground-based CCD observations.